ANALISIS POLA MAKAN DAN MITIGASI GIZI PADA BALITA KORBAN BENCANA BANJIR DI KELURAHAN RAWAJATI KECAMATAN PANCORAN JAKARTA SELATAN - Amira (2020)
In times of flood disaster often occurs health problems. Health problems that occur one of these are nutritional problems. The nutritional problem of toddlers in evacuation occurs due to lack of availability of food ingredients according to age group and has not been applied to the nutritional mitigation well. The purpose of this research is to know the overview of diet and nutritional mitigation in the infant flood disaster victims in Rawajati village, South Jakarta. The research uses a descriptive design of qualitative research. Data retrieval is conducted in May - June 2020 using in-depth interview techniques and Food Frequency Questionaire. The results showed that in the condition of flood disaster has a good diet, handling toddler nutrition during the evacuation has not been done specifically, there is no special food ingredients for toddlers, the number and type is not suitable for toddlers, there is no implementation of nutritional mitigation conducted by the toddler mother and lack of counseling about the mitigation of flood disaster. To anticipate health problems in catastrophic conditions, the government should educate toddlers and local people about the provision of food ingredients as needed and mitigation of flood disaster nutrition.